Associations of absolute risk of osteoporotic fractures (FRAX®) and total cardiovascular risk (SCORE) in urban population of the Russian Federation - M. A. Myagkova; I. A. Skripnikova; O. V. Kosmatova; S. A. Shalnova; V. A. Vygodin (Кардиоваскулярная терапия и профилактика, 2019)
Aim. To study the distribution of mean values of absolute risk (AR) of osteoporotic fractures (OPF) and cumulative cardiovascular risk (CVR) depending on age, gender, climatic and geographical conditions, economic characteristics of the regions and assess their associations.Material and methods. A representative sample of the urban population of the Russian Federation from 7 regions was analyzed. We included participants from following cities: Vologda, Ivanovo, Volgograd, Tyumen, Vladivostok, Vladikavkaz, Kemerovo and Krasnoyarsk. In total, 9143 espondents took part in the one-stage study: women (n=6324) and men (n=2819) aged 40-69 years. Over the next 10 years, OPF AR was calculated on the basis of the Russian FRAX® model without taking into account the bone mineral density using batch processing. To assess the total CVR, the SCORE scale was used for countries with a high risk of cardiovascular disease in people <65 years of age. To study the associations of risks with basic economic indicators characterizing the welfare of the regions: gross regional product, per capita income and compulsory medical insurance (CMI). We used the Rosstat report and official data of the territorial CMI funds for 2013.Results. In the total sample, the average AR of the main OPF was 7,8% (8,9% in women and 5,5% of men), hip fractures — 0,7% (0,9% in women and 0,4% in men), and in women average AR was significantly higher than in men (p=0,0001). The risk of main OPF increased by 2 times to the age of 70, in men — by 1,2 times. The risk of hip fractures from 40 to 70 years increased 5,5 times in women and 4,5 times in men. There were 16% of people at high OPF risk. The average CVR in the sample of 40-64 years old was 3,2%, indicating a moderate CVR in this population. In men, CVR corresponded to a high risk (6,1%), and in women to moderate and amounted to 2,0%. In men, the CVR was significantly higher (p<0,0001) than in women and increased from 40 to 65 years old by 4,3 times, in women — 7,3 times. High and very high cumulative CVR were noted in 36% of participants. The risk of OPF did not depend on climatic and geographical factors, while the highest CVR was detected in the northernmost region (Vologda) and gradiently decreased to the south (Vladikavkaz). Both between the risk of OPF and CVR, an inverse correlation was revealed with the economic parameters of population well-being. A significant positive correlation between the risk of OPF and CVR was demonstrated.Conclusion. The risk of fracture, determined using the FRAX® algorithm, is positively associated with cumulative CVR (SCORE) in both men and women. The contribution of the socio-economic factors of the region and the level of population well-being to the formation of both bone and cardiovascular risk is shown, while climatic and geographical features played a role only in increasing the CVR. The results suggest that improving of personal medical care will reduce the risk of complications of osteoporosis and atherosclerosis, regardless of the geography and climate of the region.